Implementation of Entrepreneurship Education to Cultivate the Entrepreneurial Spirit of Students in Madrasah Ibtidaiyah - Yanto, Arie; Remiswal, Remiswal; Basit, Abdul (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to explore and understand the implementation of entrepreneurship education at the elementary school level, specifically in Madrasah Ibtidaiyah. Several madrasahs in Padang City—namely MIN 1, MIN 3, and MIN 6—have been identified as reference institutions for successfully integrating entrepreneurial values into their educational practices. Research Methods: Employing a qualitative approach, this research relies on secondary qualitative data obtained through library research. The data analysis technique involves three stages: data reduction, data display, and drawing conclusions. To ensure data validity, source triangulation was applied across various references. Finding/Results: The findings reveal that the implementation of entrepreneurship education in madrasah ibtidaiyah follows three essential phases. The first is the planning stage, which includes formulating program goals, defining the vision and mission of the entrepreneurship program, selecting learning materials, and embedding entrepreneurial values into lesson plans (RPP). The second is the implementation stage, where entrepreneurial education is delivered through classroom instruction, subject integration, self-development activities, and fostering a school culture that promotes entrepreneurship. The third is the evaluation stage, focusing on assessing students’ internalization and application of entrepreneurial values through observable behaviors and participation in school activities.